« L'île du soleil » : une parenthèse de temporalité insolite - Hélène Fragaki (Temporalités)
In volume 2 of his book Bibliotheca Historica, Diodorus of Sicily tells the story of Iamboulos who discovered a blissful island while traveling through Arabia. This fabulous story, which can be defined as a utopian novel in the broader sense of the term, is therefore deliberately incorporated into a book which is supposed to be historical. Its original version, attributed to Iamboulos, dates back to Hellenistic times and cannot have been created later than the middle of the 1st c. B.C., when the Bibliotheca Historica was written. At the beginning of the novel, a sequence of extraordinary adventures gets time moving and sheds a mysterious light upon it by introducing periods determined by symbolic numbers. Thus, we are introduced to a utopian dimension of time - the temporal dimension of the island of the blessed: being immutable, continuous and homogeneous, time only forms the background for constructive, repetitive and rigorously cadenced activities. As it is devoid of any alarming or destructive traits, it is always accompanied by growth and prosperity, all the more so as life is extremely long and the impact of death minimized. This peaceful temporal digression, framed by symbolical stretches, seems to come as a reaction to a violently disquieting temporal reality. However, it is not as static as it might seem, for it is incorporated into the movement of historical time and can be accessed through the much more turbulent time of adventure and travel.